2010
DOI: 10.1016/j.jbiotec.2009.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, purification and characterization of recombinant glycosylated human prolactin (G-hPRL) secreted by cycloheximide-treated CHO cells

Abstract: Human prolactin (hPRL) is a 199 aminoacid protein hormone with a wide spectrum of biological activities which is best known for its stimulation of lactation and development of mammary gland. This protein contains only one potential asparagine-linked glycosylation site, which is partially (10-30%) occupied when the protein is synthesized in eukaryotic cells. Although the biological activity of glycosylated hPRL (G-hPRL) has been found to be approximately 4-fold lower than that of hPRL, its physiological functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
2
5
0
7
Order By: Relevance
“…This confirmed the presence of about twice as much hPRL in the medium treated with 1 mM NaBu and the efficient adsorption of both the 25 kDa glycosylated (G-hPRL) and the 23 kDa nonglycosylated hPRL (NG-hPRL) isoforms by the cationic exchanger [31]. …”
Section: Resultsmentioning
confidence: 55%
“…This confirmed the presence of about twice as much hPRL in the medium treated with 1 mM NaBu and the efficient adsorption of both the 25 kDa glycosylated (G-hPRL) and the 23 kDa nonglycosylated hPRL (NG-hPRL) isoforms by the cationic exchanger [31]. …”
Section: Resultsmentioning
confidence: 55%
“…hPRL is a 199 amino acid-polypeptide, whose theoretical molecular mass (MM) of 22,897.75 Da, calculated from the amino acid sequence (Wu et al 2003), has been perfectly confirmed by our research group via MALDI–TOF-MS on different CHO-, C127-, E. coli - and pituitary-derived preparations. This provided an average value of 22,910.3 Da, which is only 0.055% higher than the theoretical one (Capone et al 2015; Heller et al 2010; Soares et al 2006; Wu et al 2003).…”
Section: Introductionmentioning
confidence: 59%
“…Последовательность аминокислот схожа с таковой у плацентарного лактогена и гормона роста, что на протяжении длительно-го периода времени создавало трудности при идентификации пролактина. Период его полу-распада в крови составляет 20-30 мин [4][5][6].…”
Section: №1 3 / февраль 2012unclassified